Study of Locality and "Citizenship": an analysis of the Geography National Curriculum Model official discourse - João Pedro Pezzato; Guilherme do Val Toledo Prado (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The official discourse reported by the National Curriculum Model, especially that on geography, has incorporated several terms and expressions currently used in academic discourse. Such incorporation might indicate updating and commitment to current and theoretical regulations; however, it demands special attention. The terms "teaching democratization" or "educating for citizenship" are reported in official documents as having the same meaning; they should be better explained. Once they are widely broadcast, new concepts, codes, and expressions have become central elements of pedagogical discourses. Therefore, educational agents should do a more thorough and detailed analysis of the terms mentioned above to better explain their meanings, involving practical or theoretical aspects.